Urban solid waste management based on geoinformatics technology - Shamshiry, Elmira; Nadi, Behzad; Mokhtar, Mazlin; Komoo, Ibrahim; Hashim, Halimaton Saadiah (Academic Journals, 2011)
The solid waste materials in cities are the natural outcome of human activities. Provision of such system appears to be a major problem due to the complication and the wide nature of waste production. Due to the different parameters involved, deciding upon a suitable location is also very complicated, costly and time consuming. Different criteria are working in determination of an appropriate place for disposal; each of them is of high importance and may cause specific restrictions as to the selection of the location. The ultimate aim of these criteria is the selection of a site that is likely to have at least possible detrimental environmental effect on the nearby area. The pollution of underground water and soil of surrounding area can be considered as some of these bad effects. However, geospatial system can serve as an efficient way of employing and managing various data that can be utilized in locating more appropriate places for the disposal of solid waste. The methodology being implemented utilized geospatial technology for management and visualization of spatial data while fuzzy logic sets is used in searching the best location for landfill.